Komunikasi, Lingkungan Kerja, Disiplin dan Kinerja pada Karyawan PT. Pangan Lestari (Finna Food) Sidoarjo: (Communication, Work Environment, Discipline and Performance in Employees of PT. Food Lestari (Finna Food) Sidoarjo) - Musrifa, Nova; Firdaus, Vera; Ubaidillah, Hasan (UPT Penerbitan Universitas Jember, 2024)
This study aims to determine the effect of communication, work environment, and work discipline on employee performance. This research uses quantitative methods with a descriptive approach. The main research data used a questionnaire, which was analyzed by multiple linear regression, and processed with PLS (Partial Least Square). The research population was employees of PT Pangan Lestari Sidoarjo with a total of 171 respondents. The sampling technique used proportional random sampling. The results of this study indicate that communication affects employee performance improvement. The work environment has an influence on employee performance, and employee discipline can improve employee performance.